PEMBERDAYAAN MASYARAKAT PETANI GULA AREN DI DESA TAMBELANG KECAMATAN TOULUAAN SELATAN KABUPATEN MINAHASA TENGGARA - TULUNG, BRIAN DEVID; LALOMA, ALDEN; KOLONDAM, HELLY (Sam Ratulangi University, 2019)
Community empowerment actually refers to the word empowerment, which is an effort toactualize the potential that is already owned by the community. Thus, the approach of communityempowerment in the development of palm sugar farming communities is the emphasis, on the importanceof self-reliant local communities, as a system that organizes themselves. Such a community empowermentapproach is certainly expected to give a role to individuals not as objects, but as actors who determine theirlives. Community empowerment efforts can be seen from the side of their existence as a process.Empowerment as a process can be seen from the stages of activities in order to achieve a goal, which isusually determined by the time period. Society in English terms is a society that comes from the Latin wordsocius which means (friend). The term community comes from the Arabic word which means (toÂ participate and participate). Society is a group of people who get along with each other, in scientific termsit interacts with each other. A human entity can have infrastructure through which its citizens can interactwith one another. Another definition, society is the unity of human life that interacts according to aparticular system of customs which is continuous, and which is bound by a sense of shared identity.Continuity is a community unity that has all four characteristics, namely: Interaction between its citizens,customs, continuity of time, a strong sense of identity that binds all citizens. The most important factor thatmust be considered in carrying out community empowerment programs is that without business capital it isvery difficult for the community to be able to improve their standard of living. Empowering people is notenough just to provide venture capital but must be accompanied by an increase in the capacity of humanresources so that they are able to think and act in making various efforts and efforts to improve their welfareindependently without any dependence on others. The provision of facilities and infrastructure for thecommunity to be able to do their business is one part of the government's responsibility which must becarried out through community empowerment programs.Keywords: Empowerment, Community, Business Capital, Facilities and Infrastructure.